2001
DOI: 10.1111/j.1475-2743.2001.tb00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil nutrient changes due to land use changes in Northern China: a case study in Zunhua County, Hebei Province

Abstract: Abstract. Since the 1980s, land use in rural areas of China has changed greatly as the result of political initiatives. These changes have caused soil nutrient changes which are examined in this paper for Zunhua County, northern China from 1980 to 1999. The areas of farmland, grassland, and paddy decreased greatly and were replaced by increases in forest and residential land. The soils under forest in 1999 transformed from farmland in 1980 increased in organic matter by 21%, total nitrogen by 18%, available n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Runquan (2002) reported a decrease in soil organic matter and total nitrogen due to deforestation. Fu et al (2001) also found 18% increment in total soil N when farm lands were converted back to forest land.…”
Section: Results and Discussion Effect Of Land Use Systems On Soil Phmentioning
confidence: 88%
“…Runquan (2002) reported a decrease in soil organic matter and total nitrogen due to deforestation. Fu et al (2001) also found 18% increment in total soil N when farm lands were converted back to forest land.…”
Section: Results and Discussion Effect Of Land Use Systems On Soil Phmentioning
confidence: 88%
“…Runquan (2002) reported a decrease in soil organic matter and total nitrogen due to deforestation. Fu et al (2001) also found 18% increment in total soil N when farm lands were converted back to forest land. This increase in total soil N might be due to fixation of atmospheric nitrogen by the trees, shrubs, and grasses when farm lands were converted back to forest land.…”
Section: Effects Of Land Use Systems On Soil Chemical Propertiesmentioning
confidence: 88%
“…Despite ongoing research efforts on land-cover and land-use patterns, there remains a need for development of basic land-cover datasets providing quantitative, spatial land-cover information (Xavier and Szejwach, 1998). The ARC/INFO (ESRI, 1994) Geographical Information System (GIS) software was used in our work for the analysis of land use area change and the transition matrix analysis between land use types from 1980 to 2000 because the research benefits of a GIS approach have been illustrated by many ecological studies (Coleman et al, 1994;Bradshaw and Muller, 1998;Swetnam et al, 1998;Fu et al, 2001). In this study, land use datasets were obtained by incorporating Sanjiang Plain during relatively cloud-free days in September 1980 (MSS data), August 1996 (TM data), and September 2000 (TM data).…”
Section: Land-use Change Estimates Using Landsat Mss and Landsat Tm Datamentioning
confidence: 99%